A Comprehensive Analysis of the CaMK2A Gene and Susceptibility to Alzheimer’s Disease in the Han Chinese Population - Fang, Xinyu; Tang, Wei; Yang, Fuyin; Lu, Weihong; Cai, Jun; Ni, Jianliang; Zhang, Jiangtao; Tang, Wenxin; Li, Tao; Zhang, Deng-Feng; Zhang, Chen (Frontiers in Aging Neuroscience, 2019)
There is ample evidence suggesting that calcium/calmodulin-dependent protein kinase II alpha (CaMK2A) may play an important role in the pathophysiology of Alzheimer's disease (AD). This genetic study aimed to investigate whether CaMK2A confers susceptibility to the development of AD in the Han Chinese population. A total of 7 SNPs within CaMK2A were screened in two independent cohorts from southwestern China (333 AD patients and 334 controls) and eastern China (382 AD patients and 426 controls) to discern the potential association between this gene and AD. In addition, a cross-platform normalized expression resource was used to investigate whether CaMK2A is differentially expressed in the brain between individuals with AD and the controls. In addition, expression quantitative trait loci (eQTL) analysis was used to explore the differences in CaMK2A expression in the brain among different genotypes. The cross-platform normalized data showed significant differences in CaMK2A expression in the hippocampus, entorhinal cortex and temporal cortex between the AD patients and the control subjects (|logFC| > 0.1, P < 0.05); however, only the differences in the hippocampus and temporal cortex remained after the multiple comparisons correction (FDR-corrected, P < 0.05). The frequency of the rs4958445 genotype were significantly different between the AD subjects and the controls from southwestern China (P = 0.013, P = 0.034 after FDR correction). When the two samples were combined, rs4958445 still showed a significant association with AD (P = 0.044). Haplotype analysis indicated that the T-A-C-A-T-C-C and T-G-C-A-T-C-C haplotypes in the southwestern cohort and the T-G-C-G-C-T-C haplotype in the eastern cohort, consisting of rs10051644, rs6869634, rs3797617, rs3756577, rs4958445, rs10515639 and rs6881743, showed a significant association with AD (P = 0.037, P = 0.026 and P = 0.045, respectively). Furthermore, the brain eQTL analysis revealed a significant association between the rs4958445 polymorphism and CaMK2A expression in the inferior olivary nucleus (P = 0.029). Our results suggest an important role for CaMK2A in the pathophysiology of AD in the Han Chinese population, especially the southwestern population.